1983
DOI: 10.1073/pnas.80.8.2235
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond absorption spectroscopy of hemoglobin: elementary processes in kinetic cooperativity.

Abstract: A nanosecond absorption spectrometer has been used to measure the optical spectra of hemoglobin between 3 ns and 100 ms after photolysis of the CO complex. The data from a single experiment comprise a surface, defined by the time-ordered set of 50-100 spectra. Singular value decomposition is used to represent the observed spectra in terms of a minimal set of basis spectra and the time course of their amplitudes. Both CO rebinding and conformational changes are found to be multiphasic. Prior to the quaternary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

27
248
2

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(277 citation statements)
references
References 24 publications
27
248
2
Order By: Relevance
“…Unliganded crystals of human hemoglobin grown under certain low-salt conditions can maintain their integrity upon oxygen binding; however, oxygen binding in this case is noncooperative (12). Although the ability to follow allosteric transitions in the crystalline state is limited when such large quaternary structural changes accompany cooperative ligand binding, spectroscopic investigations of hemoglobin solutions have revealed some aspects of the kinetic pathway of allosteric structural transitions (13)(14)(15). Results to date suggest a multistep pathway, with key tertiary structural transitions taking place within a few microseconds and quaternary rearrangements occurring in the range of tens of microseconds.…”
Section: Allosteric Protein Transitions ͉ Intersubunit Communication mentioning
confidence: 99%
“…Unliganded crystals of human hemoglobin grown under certain low-salt conditions can maintain their integrity upon oxygen binding; however, oxygen binding in this case is noncooperative (12). Although the ability to follow allosteric transitions in the crystalline state is limited when such large quaternary structural changes accompany cooperative ligand binding, spectroscopic investigations of hemoglobin solutions have revealed some aspects of the kinetic pathway of allosteric structural transitions (13)(14)(15). Results to date suggest a multistep pathway, with key tertiary structural transitions taking place within a few microseconds and quaternary rearrangements occurring in the range of tens of microseconds.…”
Section: Allosteric Protein Transitions ͉ Intersubunit Communication mentioning
confidence: 99%
“…For that purpose, we have applied a singular value decomposition (SVD) analysis on a large set of the far-UV CD spectra of cyt c (typically more than 200 spectra). Application of SVD to spectroscopic or other data sets of proteins is not at all new, and is even classical (Hofrichter et al, 1983;Henry & Hofrichter, 1992;McPhie & Shrager, 1992;Jones et al, 1993;Ansari et ai., 1994;Sreerama & Woody, 1994;Chen et al, 1996;Jager et al, 1997). Here, we use it to analyze far-UV CD spectral changes produced by co-solvents.…”
mentioning
confidence: 99%
“…Following laser photodissociation of CO, the early (147 ns) post-photolysis signal evolved toward the well defined deoxyHb vs. HbCO scattering difference pattern in about 2 μs. This estimate implies that dimer rotationthe largest structural change in the R-T allosteric transition-is much faster than 20 μs, the time constant detected by optical spectroscopy (2,3). Quite recently Fischer et al (14) published a computational analysis of Hb dynamics which revealed distinct tertiary and quaternary conformational events; in particular, they reported two sequential quaternary changes (called Q 1 and Q 2 ), which they assumed to be consistent with the time constants at 2 μs (for Q 2 ) and 20 μs (for Q 1 ) reported by Balakrishnan et al (10).…”
mentioning
confidence: 93%
“…Starting with the carbon monoxide adduct HbCO in the allosteric quaternary state called R 4 , complete photolysis yields the unliganded R 0 state; the destiny of this photoproduct is a complex time-dependent process involving competing events such as ligand rebinding and (tertiary and quaternary) conformational decays. Changes in the optical and resonance Raman spectra of the different states have provided, over the last four decades, a quantitative estimate of the rates of the competing events (2)(3)(4)(5). For a review on time-resolved optical absorption (TR-OA) data describing conformational decays as well as rebinding in the dark of a ligand escaped into the solvent (bimolecular) or trapped within the protein matrix (geminate), see Eaton et al (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation